Citizen Satisfaction Measurement Challenges in State Service Provision in Azerbaijan - Khudaverdiyeva, Aynura; Namazova, Fidan; Babayeva, Aynur (ADA University, 2023)
Digitalization of public services is one of contemporary indicators of today’s society, development and modernization. Citizen satisfaction measurement in online services is one of the main conditions and drivers of constant improvement of public services. This capstone project is focused on investigation of the challenges of citizen satisfaction measurement in public services provision in Azerbaijan. The paper examines that digital government experiences barriers because of the lack of supportive legal framework, lack of citizen engagement in evaluation mechanisms and insufficiencies in technological infrastructure. The authors propose policy alternatives for the challenges mentioned above in this direction such as establishing supportive legal and institutional framework, utilization of satisfaction and trust surveys as well as development of infrastructure and adoption of new technologies. All proposed policy alternatives are evaluated against five criteria which are effectiveness, efficiency, equity, feasibility, and flexibility. The research gathered primary data from the survey and expert interviews, as well as secondary sources regarding the existing problem. The results conclude that in order to solve citizen satisfaction measurement challenges in public services in Azerbaijan, the government should establish a proper supportive legal framework and utilize survey mechanisms.
Keywords: Electronic government information -- Azerbaijan; Public services -- Customer satisfaction -- Azerbaijan; Digital government -- Policy and governance; Public and International Affairs